Evolution of guidelines in the field of organizational design of investment and construction activities - Sibikovskyi, O.; Tsymbalysty, Y.; Pedko, Y.; Pasiekov, A. (Ways to Improve Construction Efficiency, 2024)
The evolution of guidelines in the field of organizational design for investment and construction activities reflects the complex transformations of the modern construction sector and project management approaches. In the current context of globalization, increased competition in the real estate and infrastructure markets, and the digitalization of management processes, there is a need for continuous review of principles, methods, and standards of organizational design. Particular attention is paid to the alignment of strategic, tactical, and operational guidelines at all stages of investment and construction projects, including resource planning, risk management, ensuring economic efficiency, and compliance with regulatory requirements. A significant element of development is the integration of digital technologies, such as Building Information Modeling (BIM), resource management systems (ERP), analytical platforms, and project lifecycle modeling, which enhances decision-making accuracy and coordination efficiency among all project participants. Digitalization of design ensures transparency of processes, optimizes time and resource expenditure, and allows the integration of innovative approaches to the organization of construction work. Considerable attention is given to the development of adaptive guidelines capable of responding to changes in market conditions, legislation, and social demands. Organizational design is considered a multi-level process that combines strategic planning, operational management, and analytical support. A critical aspect is ensuring interaction between investors, developers, contractors, government authorities, and local communities, enabling a balance between the economic, social, and environmental objectives of the project. The role of standardization, methodological tools, and digital platforms in shaping modern guidelines is highlighted, along with the necessity of continuously updating management practices to maintain the competitiveness of enterprises. Conclusions emphasize that the evolution of organizational design guidelines is a key factor in improving the efficiency and sustainability of investment and construction activities. It ensures the integration of strategic and operational goals, enables the forecasting and minimization of risks, enhances the adaptability of companies to changing market conditions, and promotes the implementation of innovations in project management processes.